Elimination of Sexual Violence in Feminist Legal Theory - Widyawati, Anis; Pujiyono, Pujiyono; Rochaeti, Nur (JILS (Journal of Indonesian Legal Studies), 2021)
The closeness of women to poverty shows that development still maintains women's subordination and places women in a marginal position. What is the analysis of the Feminist Legal Theorist (FLT) in the elimination of sexual violence? Feminist Legal Theory (FLT) as one of the streams in Philosophy of Law is one of the schools of thought that was born from the main philosophy of the paradigm of Critical Theory Feminist Legal Theory (FLT) as one of the streams in the paradigm of critical theory. It is used to analyze the complexity of the needs of victims, both women, girls, boys, and girls. The Bill on the Elimination of Sexual Violence uses the Feminist Legal Theory (FLT) as an analysis so that in every norm that is formulated this bill always considers what specific experiences of women, especially victims of sexual violence. Legal protection against the elimination of sexual violence is a form of implementation of the second principle of Pancasila, namely a just and civilized humanity.